Profiles and influencing factors of pulmonary fibrosis associated with biologic and conventional disease-modifying antirheumatic drugs for autoimmune diseases: a disproportionality study based on FAERS and VigiAccess - Zhang, Xinyue; Wu, Xinhui; Luo, Cheng; Yang, Chun; Jia, Nan; He, Jiayi; Chen, Qian; Wang, Fei (Frontiers in Pharmacology, 2025)
BackgroundPulmonary fibrosis is a severe and potentially fatal adverse event, and its association with disease-modifying antirheumatic drugs (DMARDs) has raised long-standing concerns. However, systematic investigations on this topic are lacking. This study aims to analyze the drug-specific safety signals, characteristics, and potential patient risk factors of DMARDs-related pulmonary fibrosis.MethodsWe extracted reports of pulmonary fibrosis events related to 36 types of DMARDs from the U.S. FDA’s adverse event reporting system (FAERS) and WHO-VigiAccess databases. Full database-wide and active-comparator restricted disproportionality analyses were conducted to identify the strength of safety signals for different DMARDs. Multivariable logistic regression was used to analyze risk factors for pulmonary fibrosis events associated with DMARDs.ResultsIn FAERS, 4,869 cases of pulmonary fibrosis were reported among 2,456,021 adverse event reports involving DMARDs. Similarly, VigiAccess documented 4,847 pulmonary fibrosis cases out of 3,488,917 DMARD adverse events. Methotrexate (reporting odds ratio in VigiAccess [ROR VigiAccess] = 4.39, 95% CI: 4.11–4.70), leflunomide (ROR VigiAccess = 3.26, 95% CI: 2.75–3.86), sulfasalazine (ROR VigiAccess = 2.33, 95% CI: 1.91–2.84), rituximab (ROR VigiAccess = 1.43, 95% CI: 1.27–1.61), and tocilizumab (ROR VigiAccess = 1.28, 95% CI: 1.08–1.51) consistently showed significant disproportionality signals across both databases, suggesting a potential safety concern for pulmonary fibrosis. Multivariable analysis identified older age (>65 years) as a strong and consistent risk factor across all DMARD classes, while the influence of sex varied by drug. The time to onset of pulmonary fibrosis differed significantly across different DMARDs, with B-cell inhibitors showing the shortest onset (median: 113 days, IQR = 54–397) and TNF-α inhibitors the longest (median: 523 days, IQR = 143–1,185).ConclusionThis study revealed varying degrees of pulmonary fibrosis signals related to DMARDs, with significantly overreporting observed in certain conventional and biologic DMARDs. Age was identified as a key susceptibility factor. As the use of these agents expands, clinicians should remain vigilant in monitoring for pulmonary fibrosis.